2012
DOI: 10.1007/s00228-012-1237-2
|View full text |Cite
|
Sign up to set email alerts
|

A prospective analysis of the preventability of adverse drug reactions reported in Sweden

Abstract: +46 10 103 43 26Conflict of interest, summary: Henrik Lövborg declares that his wife is an employee of a company (MEDAC) whose products are part of this study (as is the case for many other companies). We believe a statement is not necessary to publish since this type of study includes all drugs on the market, thereby limiting the risk of conflict of interest. AbstractPurpose Adverse drug reactions (ADRs) are a major patient safety issue and a substantial proportion of ADRs are in fact preventable. The aim of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
5
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 33 publications
3
5
0
1
Order By: Relevance
“…A failure to take a previously documented allergy to a drug into account was one of the main causes of avoidable SCARs. This finding is consistent with previous studies showing that 10% of adverse drug reactions were linked to unintentional rechallenge . As in our study, these errors are mostly associated with the prescription of antibiotics, in particular β‐lactam antibiotics .…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…A failure to take a previously documented allergy to a drug into account was one of the main causes of avoidable SCARs. This finding is consistent with previous studies showing that 10% of adverse drug reactions were linked to unintentional rechallenge . As in our study, these errors are mostly associated with the prescription of antibiotics, in particular β‐lactam antibiotics .…”
Section: Discussionsupporting
confidence: 93%
“…This finding is consistent with previous studies showing that 10% of adverse drug reactions were linked to unintentional rechallenge. 34,35 As in our study, these errors are mostly associated with the prescription of antibiotics, in particular b-lactam antibiotics. 36 Inappropriate rechallenge in patients with a previous known allergy to a drug often occurs because prescribers are not aware of the patient's allergy history or because physicians neglect the risk of cross-allergy.…”
Section: Discussionsupporting
confidence: 51%
“…ADRs are a major patient safety issue and they can have significant consequences both for the patient and health care system [1]. A recent systematic review of ADRs in children reported incidences of ADRs in hospitalised children ranging from 0.6 to 16.8% among studies [2].…”
Section: Introductionmentioning
confidence: 99%
“…Also in line with our data, a systematic review found, drugs accountable for preventable drug-related hospital admissions to be aspirin (16%), diuretics (16%), NSAIDs (11%) and anticoagulants (8%) [ 39 ]. In a Swedish study on reported ADRs, a high number of preventable ADRs was found for CNS-active, cardiovascular and antithrombotic drugs, but not for cancer-related drugs [ 40 ].…”
Section: Discussionmentioning
confidence: 99%